1989
DOI: 10.1128/jcm.27.6.1250-1256.1989
|View full text |Cite
|
Sign up to set email alerts
|

Rapid flow cytometric bacterial detection and determination of susceptibility to amikacin in body fluids and exudates

Abstract: A flow cytometry-based method for rapid and quantitative detection of bacteria in various clinical specimens and for rapid determination of antibiotic effect is described. Achieving such a measurement with high sensitivity required discrimination between bacteria and other particles which were often present in clinical samples in high concentrations. This discrimination was facilitated by detecting the bacterial characteristic light scatter and fluorescence signals following staining, e.g., with the fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Nevertheless, these papers support our idea that bacterial cell count monitoring can be used as a very fast procedure to reliably predict antimicrobial susceptibility. The application of cell count monitoring may even go further as Cohen et al [14] showed in 1989 that flow cytometry could reliably predict the presence of antimicrobial susceptibility for amikacin directly in clinical samples containing polyflora. They showed that amikacin susceptibility was reliably detected within 1 h in 92% of 13 clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these papers support our idea that bacterial cell count monitoring can be used as a very fast procedure to reliably predict antimicrobial susceptibility. The application of cell count monitoring may even go further as Cohen et al [14] showed in 1989 that flow cytometry could reliably predict the presence of antimicrobial susceptibility for amikacin directly in clinical samples containing polyflora. They showed that amikacin susceptibility was reliably detected within 1 h in 92% of 13 clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases this function cannot be detected due to irreversible cell damage or fastidious growth conditions. This type of assay can be used to demonstrate antibiotic susceptibility within 2 h from sampling [79]. Another way to detect replication is by cell tracking, where covalently labelled cells halve their £uorescence upon cell division [80].…”
Section: Reproductionmentioning
confidence: 99%
“…Dye extrusion can be overcome either by using dyes that cross-link inside the cell [79] or by using appropriate metabolic inhibitors. Thus, staining procedures such as the Chemchrome kit by Chemunex (Maisons-Alford, France) can achieve a good staining for a large spectrum of pathogens [99].…”
Section: Esterase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry has been used as a rapid method for testing Diaper and Edwards 1994;Porter et N/. 1995), investigating dormancy and stanation (Kaprelyants and Kell 1993 ;Diaper and Edwards 1994), testing susceptibility to antibiotics (Martinez et al 1982;Steen et al 1982; Cohen and Sahar 1989;Gant et a/. 1993;Mason et al 1994) and for studjing the effect of heat, sonication and electroporation on bacterial vitality (Lopez-Amoros et al.…”
Section: Introductionmentioning
confidence: 99%